APPLICATION OF BEAM DEFLECTION DETERMINATION FOR ESTIMATION OF MACHINING ACCURACY - MURČINKOVÁ, Zuzana (Trends in education, 2010)
The paper dealt with application of beam deflection determination for estimation of machining accuracy in range of teaching. The paper concerns the typical problems from mechanics of deformable continuum and theory of machining.
Keywords: bending; machining; deflection; accuracy.